2019
DOI: 10.1111/jch.13606
|View full text |Cite
|
Sign up to set email alerts
|

Association between cerebral microbleeds and hypertension in the Swedish general population “Good Aging in Skåne” study

Abstract: Cerebral microbleeds (CMB) on MRI are frequent in healthy aging individuals but precede ischemic and hemorrhagic stroke and dementia. Different etiologies have been suggested for nonlobar CMB, which have a stronger connection to hypertension (HT) than do lobar CMB. This study aimed to investigate the prevalence of CMB and the association between nonlobar/lobar CMB and different blood pressure (BP) and HT treatment conditions in a longitudinal, population‐based cohort of the Good Aging in Skåne (GÅS) study. Whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…In the middle-aged and elderly individuals in Rotterdam Scan Study (5), hypertension was associated with the presence of CMBs. One Swedish study found that hypertension was the major risk factor for CMBs in the general population (6). Longitudinal community studies (7,8) also demonstrated that baseline hypertension was associated with development of new CMBs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the middle-aged and elderly individuals in Rotterdam Scan Study (5), hypertension was associated with the presence of CMBs. One Swedish study found that hypertension was the major risk factor for CMBs in the general population (6). Longitudinal community studies (7,8) also demonstrated that baseline hypertension was associated with development of new CMBs.…”
Section: Discussionmentioning
confidence: 99%
“…Cross-sectional (5,6) and longitudinal studies (7,8) revealed that blood pressure (BP) over 140/90 mmHg was a crucial risk factor of CMBs in the general population. Since the Systolic Blood Pressure Intervention Trial (SPRINT) showed that aggressive control of BP resulted in lower rates of major cardiovascular events and mortality (9), cut-off for hypertension was lowered from 140/90 to 130/80 mmHg in the 2017 American College of Cardiology/American Heart Association (ACC/AHA) guideline (10).…”
Section: Introductionmentioning
confidence: 99%
“…They are closely related and have the same pathological characteristics and often occur in patients with hypertension (8)(9)(10). Although CMBs and WMCs may occur with increased frequency in hypertension (11,12), knowledge of their relationship with the duration of hypertension in patients in different stages of hypertension is limited. Some studies have reported WMCs in subjects displaying CMBs in patients with hypertension (13), but no study has primarily focused on the WMC-CMB relationship in patients with different stages of hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…patients with frontotemporal dementia, patients with Lewy-body dementia, patients with diagnostic uncertainty, patients with severe psychiatric and behavioral symptoms, and patients with familial disorders) should be given high priority for follow-up in a specialist setting, for example, a memory clinic setting. Vascular risk factors are associated with an increased risk of cognitive decline and dementia [26] and with the rate of progression of dementia and the occurrence of brain pathology such as small vessel disease [27,28], lacunar infarcts [29,30] and microbleeds [31]. Hence, optimal management of vascular risk factors may potentially modify the disease course in dementia.…”
Section: Supplemental Considerations For Systematic Medical Follow-upmentioning
confidence: 99%
“…We believe that systematic management of vascular risk factors is as important in patients with mild to moderate dementia as in patients without dementia as these factors are associated with adverse health outcomes and because an effect is unlikely to differ between patients with and without dementia [26][27][28][29][30][31]. It is the opinion of the authors that the value and attitudes of patients with dementia would not go against treatment, at least for a majority of patients.…”
Section: Justification For Statementmentioning
confidence: 99%